2022
DOI: 10.3171/2022.10.jns221138
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of stent-assisted coiling and Woven EndoBridge embolization for the treatment of unruptured wide-neck bifurcation intracranial aneurysms

Abstract: OBJECTIVE Woven EndoBridge (WEB) intrasaccular flow disruptors and stent-assisted coiling (SAC) are viable endovascular treatment options for wide-neck bifurcation intracranial aneurysms (WNBAs). Data directly comparing these two treatment options are limited. The authors aimed to compare radiographic occlusion rates and complication profiles between patients who received WEB and those who received SAC for WNBAs. METHODS Retrospective review of a prospectively maintained cerebrovascular procedural database w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…15 Kashkoush et al conducted a study involving 10 participants, which showed that both SAC and the Woven En-doBridge had extremely high rates of complete occlusion at last follow-up (94% for Woven EndoBridge vs 91% for SAC), with no statistically significant difference between the two modalities (p = 0.744). 5 Salem et al conducted a study involving 10 participants, which revealed that both the Pipeline Embolization Device (PED, Medtronic) group and the SAC group had similar complete occlusion rates at their last imaging follow-up evaluations (78.2% vs 78.1%). 16 A study by Piotin et al involving 7 participants found that the recurrence rate of the stent group was lower than that of the non-stent group (19.4% vs 33.5%), with a significant statistical difference between the two (p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Kashkoush et al conducted a study involving 10 participants, which showed that both SAC and the Woven En-doBridge had extremely high rates of complete occlusion at last follow-up (94% for Woven EndoBridge vs 91% for SAC), with no statistically significant difference between the two modalities (p = 0.744). 5 Salem et al conducted a study involving 10 participants, which revealed that both the Pipeline Embolization Device (PED, Medtronic) group and the SAC group had similar complete occlusion rates at their last imaging follow-up evaluations (78.2% vs 78.1%). 16 A study by Piotin et al involving 7 participants found that the recurrence rate of the stent group was lower than that of the non-stent group (19.4% vs 33.5%), with a significant statistical difference between the two (p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…accepted for treating unruptured wide-necked aneurysms due to its good safety and efficacy. 5,6 However, its use for treating ruptured aneurysms is controversial due to the significantly higher incidence rates of complications and mortality compared with its use for unruptured aneurysms. [7][8][9] Stent placement during surgery increases the complexity of the intervention and the risks of complications, prompting the use of antiplatelet drugs as a preventive measure.…”
mentioning
confidence: 99%
“…13 Several studies comparing WEB and SAC in mixed populations have shown similar rates of AO between the treatments but with a higher rate of periprocedural complications in SAC (0% for WEB vs 9% for SAC). [24][25][26] However, a meta-analysis by Zhao et al 27 reported variable and suboptimal long-term complete or nearcomplete occlusion rates after SAC for wide-neck aneurysms (71.9%; 95% CI, 52.6%-91.1%). By contrast, our study demonstrated a consistently high rate of AO in both short-and longterm FUPs (90.0%-92.8%), with a 0% periprocedural complication rate related to aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular treatment of wide-neck bifurcation intracranial aneurysms (WNBAs) is a challenging procedure due to the high recurrence rate. 1 Although stent-assisted coil embolization or flow diverter placement have been reported to reduce the recurrence rate, complete occlusion (CO) rates are 67.2% for stent-assisted coil embolization, 2 and 61.5%-73.2% for flow diverter placement, 3,4 which are not satisfactory compared with clipping. 5 Recently, the Woven Endo Bridge (WEB; MicroVention, Tustin, CA, USA) was developed based on a novel treatment concept called the flow disruptor.…”
Section: Introductionmentioning
confidence: 99%